Permohonan Kepailitan demi Kepentingan Umum dalam Persperktif Asas Kepentingan Umum - Hilda Ainy Apriliany (Universitas Kuningan, 2019)
AbstractThe public interest is the interest of the Nation, the State, and society that must be realized by the government and used as much as possible for the prosperity of the people. The public interest still raises many interpretations in society. There are no clear boundaries or characteristics regarding the development criteria for the public interest as stipulated in the legislation. Basically the public interest must meet 2 criteria, namely what the activity is intended for and can provide benefits to the community. In the public interest, state law is not bound by a country's territorial boundaries because the law adjusts to all circumstances and events that involve a public interest. Including the national and state interests as well as the common interests of the people, taking into account social, political, psychological aspects based on the principles of National Development by heeding National Resilience and Archipelago Insight. The principle of public interest The principle that bases itself on the authority of the state to protect and regulate the interests in people's lives.Keywords: Bankruptcy, Principle of Public Interest, National Resilience AbstrakKepentingan umum adalah kepentingan Bangsa, Negara, dan masyarakat yang harus diwujudkan oleh pemerintah dan digunakan sebesar-besarnya untuk kemakmuran rakyat. Kepentingan umum masih menimbulkan banyak penafsiran dalam masyarakat. Tidak ada batasan atau karakteristik yang jelas mengenai kriteria pembangunan untuk kepentingan umum yang diatur dalam peraturan perundang-undangan tersebut. Pada hakekatnya kepentingan umum harus memenuhi 2 kriteria yaitu kegiatan tersebut ditujukan untuk apa dan dapat memberikan manfaat bagi masyarakat. Kepentingan umum, hukum negara tidak terikat pada suatu batas-batas wilayah suatu negara karena hukum menyesuaikan diri sama semua keadaan maupun kejadian yang menyangkut suatu kepentingan masyarakat. Termasuk kepentingan bangsa dan negara serta kepentingan bersama dari rakyat, dengan memperhatikan segi-segi sosial, politik, psikologis atas dasar asas-asas Pembangunan Nasional dengan mengindahkan Ketahanan Nasional serta Wawasan Nusantara. Asas kepentingan umum asas yang mendasarkan diri pada wewenang negara untuk melindungi dan mengatur kepentingan dalam kehidupan masyarakat.Kata Kunci : Pailit, Asas Kepentingan umum, Ketahanan Nasional